La occidentalización de la arquitectura rusa. Perspectiva desde cuatro estadios del Mundial de fútbol FIFA Rusia 2018 - Castañeda, César (2020)
Football soccer, with the growth of globalization, has become the sport with the greatest socio-economic impact worldwide, due to its huge audience and the technological, digital and commercial system created around it, beyond of exclusively sportive. In this way, the architecture of the stadiums reflects these transformations from rational models of construction to sculptural-digital objects. The 2018 World Cup in Russia, as a great sports event, allows us to review the conditions of architectural insertion of a nation that longs to return as a world power and that has had to forcefully join a capitalist economy of which it was, for decades, foreign and critical. The analyzed stadiums of four different and distant cities (Saransk, Yekaterinburg, Sochi and Moscow) allow us to understand the actions of the design firms, their project logic, the objects created and the need to achieve high-impact technological buildings. All this is in relation to a geographical and cultural place like Russia, with the uncertainty posed by the accelerated acceptance of the globalization in a country with traditional roots.